Estudios sobre la Universidad de Tortosa (1600-1717) - Ramis Barceló, Rafael (Historia de las Universidades, 2020)
This book aims to study the history of the University of Tortosa from its canonical erection in 1600 to 1717, when it was transferred to Cervera. Through four chapters the place of the University of Tortosa in the set of the Universities of the Crown of Aragon is studied, through the proposopography of rectors, lecturers and graduates. It was a Convent-University run by the Order of Preachers that exclusively taught Philosophy and Theology. The documentary appendix includes the Statutes of the Colegio de San Matías and San Jaime, the Statutes of the University, as well as the list of graduates that has been preserved for the periods 1600-1623 and 1659-1717. Among them, there are numerous regular and secular clergymen from Valencia, Catalonia, Aragon and Mallorca.---Este libro pretende estudiar la historia de la Universidad de Tortosa desde su erección canónica en 1600 hasta 1717, año en el que fue transferida a Cervera. A través de cuatro capítulos, se estudia el lugar de la Universidad de Tortosa en el conjunto de las Universidades de la Corona de Aragón, mediante la proposopografía de rectores, lectores y graduados. Era un Convento-Universidad que estaba en manos de la Orden de Predicadores, y en el que se enseñaba exclusivamente Filosofía y Teología. El apéndice documental incluye los Estatutos del Colegio de San Matías y San Jaime, los Estatutos de la Universidad, así como la relación de los graduados que se ha conservado para los períodos 1600-1623 y 1659-1717. Entre ellos, se encuentran numerosos clérigos regulares y seculares de Valencia, Cataluña, Aragón y Mallorca.